The Knowledge Level of Anemia Among Female Students at SD Negeri 1 Cilowa, Kuningan Regency - Marsyah Dzikri, Al Rivan; Mardhotillah, Hanifah; Akbar Rizkyan Affandy; Andini Hikmatu Diniah; Dwi Putri Andini; Shela Dwi Amaliyanti (International Journal of Health Engineering and Technology, 2025)
Anemia is a common nutritional problem that often occurs among school-aged children, especially female students, and can negatively impact growth, concentration, and academic performance. Early knowledge of anemia is essential to support preventive efforts from a young age. This study aimed to describe the knowledge level of anemia among female students at SD Negeri 1 Cilowa, Kuningan Regency. This research used a descriptive quantitative method involving 37 female students selected through total sampling. Data were collected using a validated structured questionnaire consisting of 10 multiple-choice questions covering the definition, causes, symptoms, impacts, and prevention of anemia. The collected data were analyzed descriptively and presented in the form of frequency distributions and percentages. The results showed that most respondents had a good level of knowledge about anemia, with 81.1% categorized as having good knowledge and 18.9% categorized as having moderate knowledge. There were no respondents with low knowledge levels. The average knowledge score achieved by the students was 94.86 out of a maximum score of 100. The conclusion of this study is that most female students at SD Negeri 1 Cilowa have a good level of knowledge about anemia. However, continuous health education is still necessary to ensure that all students have an optimal and comprehensive understanding.